2021
DOI: 10.1371/journal.ppat.1009240
|View full text |Cite
|
Sign up to set email alerts
|

Temporally integrated single cell RNA sequencing analysis of PBMC from experimental and natural primary human DENV-1 infections

Abstract: Dengue human infection studies present an opportunity to address many longstanding questions in the field of flavivirus biology. However, limited data are available on how the immunological and transcriptional response elicited by an attenuated challenge virus compares to that associated with a wild-type DENV infection. To determine the kinetic transcriptional signature associated with experimental primary DENV-1 infection and to assess how closely this profile correlates with the transcriptional signature acc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 39 publications
3
32
0
1
Order By: Relevance
“…At Day −2, the earliest time point in our study, we already observed the up-regulation of genes associated with type I interferon and response to virus in all major immune cell types ( Figure 2 C). This is in line with previous reports showing prominent expression of type I interferons at early phases of DENV infection ( Popper et al., 2012 ; Sun et al., 2013 ; van de Weg et al, 2015 ; Waickman et al., 2021 ), even though the exact timelines of the infection were characterized slightly differently in each study. In this study, we were able to pinpoint that the type I interferon pathway was most pronounced in monocytes.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…At Day −2, the earliest time point in our study, we already observed the up-regulation of genes associated with type I interferon and response to virus in all major immune cell types ( Figure 2 C). This is in line with previous reports showing prominent expression of type I interferons at early phases of DENV infection ( Popper et al., 2012 ; Sun et al., 2013 ; van de Weg et al, 2015 ; Waickman et al., 2021 ), even though the exact timelines of the infection were characterized slightly differently in each study. In this study, we were able to pinpoint that the type I interferon pathway was most pronounced in monocytes.…”
Section: Discussionsupporting
confidence: 92%
“…These allowed us to improve the depth of earlier transcriptomic analyses of the host immune response against DENV, which might partly be restricted by the low-resolution bulk RNA-seq and microarray ( Hanley et al., 2021 ; Popper et al., 2012 ; Sun et al., 2013 ; van de Weg et al, 2015 ). Although most of the time-course RNA-seq studies of immune response in dengue patients or in vitro systems were performed using the samples collected during the vaguely defined “acute infection” or “febrile phase” ( Hanley et al., 2021 ; Sun et al., 2013 ; van de Weg et al, 2015 ; Waickman et al., 2021 ), we broke this important period down to three consecutive days, analyzed the single-cell transcriptomic profiles of DENV patients for each day, and compared those with the two-week follow-up baselines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peripheral blood mononuclear cells (PBMC) are circulating immune cells with a single round nucleus in the blood and are common diagnostic and prognostic targets [3]. PBMC are important targets of single-cell studies because they are indicators of immune status and are studied in cancer [4][5], infectious disease [6][7], and autoimmunity [8][9][10], among others. Five major cell types that constitute PBMC are B cells (BC), dendritic cells (DC), monocytes (MC), natural killer cells (NK), and T cells (TC) [11].…”
Section: Introductionmentioning
confidence: 99%